Flower-like carbon cathode prepared via in situ assembly for Zn-ion hybrid supercapacitors. (15th August 2021) - Fan, Huailin; Hu, Xun; Zhang, Shu; Xu, Zhixiang; Gao, Guoming; Zheng, Yan; Hu, Guangzhi; Chen, Qifeng; AlGarni, Tahani Saad; Luque, Rafael
Abstract: Three-dimensional (3D) carbon from the assembly of low-dimensionally isolated segments have attracted much attention as these carbon materials not only inherit the superiorities of individual building blocks but also acquire new synergic effects. However, it remains a big issue to assemble isolated carbon segments into a 3D carbon superstructure by a facile strategy. Herein, the spheroidizing growth of hydrothermal carbon as an assembly drive and in situ formed melamine cyanurate nanosheets as structure-directing agent are combined to design and assemble B, N and O co-doped carbon flower as a promising cathode for Zn 2+ hybrids supercapacitors. The flower-like carbon exhibits large nanosheets area, interlinked conductive network, nanoscale architecture and rich electroactive sites. Boron doping enhances the chemical adsorption of SO4 2− onto the carbon cathode surface and the reaction between oxygen dopant and Zn ions added additional capacity for Zn-ion supercapacitors. The resulting device achieves an energy density of 119.7 Wh/kg at 890 W/kg and maintains 63.5 Wh/kg even at a power density of 16.5 kW/kg. Graphical abstract: Image 1 Highlights: A flower-like carbon material was prepared for Zn-ion supercapacitors. In situ formed melamine cyanurate directed the formation of flakiness carbon. The flakiness carbon was assembled into flower-like carbon by spheroidizing drive. The boron enhanced the chemical adsorption of anions onto the cathode surface. The electrochemical reaction between C-O and Zn 2+ improved pseudocapacitance.